Assessment of Status of Climate Change and Determinants of People’s Awareness to Climate-Smart Agriculture: A Case of Sarlahi District, Nepal - Sandhya Adhikari; Sara Rawal; Sandesh Thapa (Advances in Agriculture)
This study aims to analyze the status of climate change and determinants of people’s awareness of climate change in Sarlahi district, Nepal. A total of 102 respondents were selected randomly from the study area and interviewed using a semistructured questionnaire from May 12, 2021, to May 23, 2021. Along with the determinants, this survey emphasized finding climate-smart alternatives favoring not only the population or sectors like agriculture but also the climate itself. The chi-square test was conducted to measure the relationship between the operational variables, which revealed that there was no significant relationship between gender and knowledge of climate change, occupation and knowledge of climate change, land ownership and knowledge of climate change, guardian and knowledge of climate change, and decision role and knowledge on climate change. However, education, family size, and age had a significant effect on the knowledge of climate change. The binary logit model reported that age, years of schooling, training related to climate change, and involvement with cooperatives were found to have a significant effect on people’s awareness of climate change. Thus, improving people’s adoption of climate-smart agriculture in the education system of the study area and training the people in the study area should be a prime concern.